Pantoea spp : a new bacterial threat to rice production in sub-Saharan Africa - (:unkn) unknown (My University, 2018)
Among the 24 species of Pantoea described so far, five have been reported up to 46 times in 21 countries as phytopathogens of at least 31 crops. Indeed, P. ananatis and P. agglomerans have been reported as phytopathogenic bacteria for at least ten economically important crops, including rice. Recently, Africa Rice Center and its partners have suspected the presence of an emerging bacterium that causes rice bacterial blight in several African countries, and the causal agent has been confirmed as belonging to the genus Pantoea. The objectives of our thesis project were (i) to improve the collection of existing AfricaRice isolates by new collections (ii) to develop diagnostic and characterization tools for fine analysis of genetic, phenotypic and epidemio-follow-up studies. Our results showed that bacteria capable of producing bacterial blight symptoms of rice in Africa form a species complex composed mainly of P. ananatis, P. stewartii and P. agglomerans. Different types of diagnostic tools and characterizations were then developed and validated. The results from the use of these tools helped to point out the presence of this bacterial complex in several African countries and to provide details on its geographical structure. Thus, in total, we diagnosed a bacterial species complex, phytopathogenic of rice in 11 African countries (Benin, Burkina Faso, Burundi, Ghana, Ivory Coast, Mali, Niger, Nigeria, Senegal, Tanzania, Togo). In addition, analyzes of three genomes of african P. ananatis and the development, evaluation, and application of Multiple Locus VNTR Analysis (MLVA) tools provided insights into the phylogenetic and phylogenomic relationships that exist between P. ananatis strains isolated from rice and strains from other sources (plants, animals and environment). Indeed, preliminary results showed that several strains of P. ananatis isolated from rice in Africa, Asia and Europe were phylogenetically linked and formed a group that differenti
Keywords: African Research